Pakistani Urdu Novel in the 21st Century (Political Context) - Hussain, Azaadar (sourcecoder, 2023)
From the beginning to the present day, the Urdu novel has set many important milestones in terms of content, style and themes. In Urdu novel, especially after the establishment of Pakistan, politics has been given special importance as a subject. Many such novels were published in the 21st century, whose themes are related to national and international political situations and events, so here only mentioning a few specific novels written in a political context. In these novels the impact of the Subcontinent partition, the events of September 11, the US-Afghan war and the partition of Bengal, as well as the attitudes of democratic and authoritarian governments are presented.